Pengaruh Distributive Justice, Procedural Justice, Interactional Justice, Service Failure Severity, Perceived Switching Cost dan Perceived Value Terhadap Consumer Loyalty (Studi Kasus Pada Mahasiswa Pengguna Layanan Internet Telkomsel Flash di Kota Malang) - Sigit Triwibowo (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This study aims to determine the effect of distributive justice, procedural justice, interactional justice, service failure severity, perceived switching costs and perceived value of consumer loyalty specifically for consumers who have or still use the internet service Telkomsel Flash. This type of research used in this research is explanatory research. The samples used 150 by using purposive sampling and using a questionnaire as a data collection tool.Test equipment used to test instruments used are validity and reliability test. Then classical assumption that the regression model is used consistently and no refractions. Furthermore, for hypothesis testing was done using a multiple linear regression through F test and t.These results indicate that the interactional justice, service failure severity, perceived switching costs and perceived value has a significant impact on customer loyalty. While distributive justice and procedural justice did not have a significant impact on consumer loyalty. The coefficient of determination (R2) of 0.652 means that variants of the dependent variable can be affected by a variant of the independent variables. The remaining 34.8% is influenced by factors other than this model.Kata Kunci : distributive justice, procedural justice, interactional justice, service failure severity, perceived switching cost, perceived value, consumer loyalty